Improving Disaster Resilience Using Mobile Based Disaster Management System. (2016) - Aydin, Can; Tarhan, Cigdem; Ozgur, Ahmet Selcuk; Tecim, Vahap
Abstract: The use of ICTs can help to produce information and make better decisions for effective disaster management system. ICT is considered to necessary enhance adaptation capacity and supports feedback, ensure information access, enables active participation, reduces vulnerability. Mobile technologies are appropriate for providing these needs to improving resilience. Nowadays with the widespread use of mobile devices, benefiting as an information sharing environment after disaster is inevitable. The use of mobile technologies by citizens after a disaster increases resilience against disasters. The aim of the study is to increase disaster resilience by using mobile technologies to ensure citizens play an active role in disaster management.